Design of a Digital Illustration-Based Storybook Using the R&D Method in Civics Education for Grade V Students - Pandi Mukarram (Breakthroughs In Informatics, Networking, Algorithms, Research, And Yield (BINARY), 2026)
This study aims to develop a learning media in the form of a digital illustration-based storybook that contains the values of diversity for use in Civics Education (PPKn) for fifth-grade students at SDN 4 Bajur. The development is motivated by the lack of engaging and relevant learning media, impacting low student interest and participation. This research uses the R&D method with the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. Validation results from three experts indicate the developed digital storybook is in the